若m-n=3,mn=-2
则(m-n)^2=m^2+n^2-2mn=9
所以m^2+n^2=9-4=5
所以(m+n)^2=m^2+n^2+2mn=5-4=1
本文地址: http://www.goggeous.com/a/1/1081133
文章来源:天狐定制
版权声明:除非特别标注,否则均为本站原创文章,转载时请以链接形式注明文章出处。
2025-01-08职业培训
2025-01-08职业培训
2025-01-08职业培训
2025-01-08职业培训
2025-01-08职业培训
2025-01-08职业培训
2025-01-08职业培训
2025-01-08职业培训
2025-01-08职业培训
2025-01-08职业培训
2025-01-01 21:59:36职业培训
2025-01-01 21:59:35职业培训
2025-01-01 21:59:33职业培训
2025-01-01 21:59:31职业培训
2025-01-01 21:59:31职业培训
2025-01-01 21:59:24职业培训
2025-01-01 21:59:21职业培训
2025-01-01 21:59:21职业培训
2025-01-01 21:59:20职业培训
2025-01-01 21:59:19职业培训
2024-12-27 18:35职业培训
2024-12-04 01:33职业培训
2025-01-07 10:42职业培训
2024-12-03 12:43职业培训
2024-11-27 18:01职业培训
2025-01-01 03:08职业培训
2024-12-23 11:18职业培训
2024-11-26 08:51职业培训
2024-11-29 18:42职业培训
2024-12-18 02:03职业培训
扫码二维码
获取最新动态